Transformational Leadership of School Principals in Improving Teachers' Professional Competence at Public Elementary Schools in Cluster 07, Tiro, Pidie District - Rahmatullah, Rahmatullah; Usman, Nasir; Bahrun, Bahrun; AR, Murniati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the transformational leadership strategies of school principals in enhancing teachers’ professional competence, the obstacles encountered, and the supporting factors involved. Using a qualitative descriptive approach, the research was conducted at SDN Tiro, SDN Lhok Igeuh, and SDN Daya Blang Keudah through interviews, observations, and documentation. The findings show that principals apply transformational leadership by promoting professional development, encouraging enthusiasm for learning, and recognizing teacher efforts. Key obstacles include differences in teachers’ intellectual capacity, socioeconomic status, education levels, seniority, and frequent policy changes. Supporting factors include government support, collaboration among principals, a positive work environment, internal motivation, effective supervision, and the presence of competent teachers.